Seismic Performance of Ni-Ti SMA Wires Equipped in the Spatial Skeletal Structure - Liu, Yang; Yang, Tao; Li, Binbin; Liu, Bo; Wang, Wentao; Wang, Sheliang (Frontiers in Materials, 2021)
Nickel Titanium (Ni-Ti) Shape Memory Alloy (SMA) can be used to limit response of structure during external disturbances such as large seismic events. This paper presents a seismic performance study of Ni-Ti SMA wires equipped in the spatial skeletal structure. First, an improved Graesser-Cozzarelli (G-C) numerical constitutive model of the Austenitic phase of NiTi SMA wire is established. By contrast, the model based on uniaxial cyclic loading experimental tests is demonstrated as feasibility and validity. Next, a method consisting of a three-layer steel spatial skeletal structure model equipped SMA wires is employed for simulation and experimental tests. According to the obtained constitutive numerical model, the simulation program of vibration control is written to simulate the effect of vibration control of seismic EL-centro wave. Furthermore, a shaking table experimental test was designed to verify the vibration control effect under the same action of seismic EL-centro wave. By comparison of the results of the numerical simulation and shaking table test, dynamic responses of the displacement and acceleration for different floors with control and without control was concluded. The superior superelastic properties of SMA wires used in passive control are investigated and the correctness of the constitutive numerical model are verified as well. The results show that such a comprehensive analysis integrates seismic-resistant behavior of Ni-Ti SMA wires in this type of structure. Besides, proposed method has broad application prospects to address the issues in passive control field of building structures.